Game Analysis on Influence Mechanism of Equity Incentive on R&D Investments - Wen, Cao; Yuewen, Li (Review of Knowledge Economy, 2014)
A game model between shareholders and manager is built to analyze influence mechanism of equity incentive on R&D investments based on principal-agent theory. Research shows that there are inverted U-shaped relationships between equity incentive and R&D investments, the modest equity should be gave for stimulate manager.